Estimation of the Effective Radiation Dose in Nuclear Medicine Workers from Dhaka by Measuring Radioactivity in Urine Sample Resulting from Internal Exposure (Jagannath University Journal of Science, 2024)
This study estimates the effective doses and activity concentration from 151 urine samples which are collected from 15 (Fifteen) occupational workers at National Institute of Nuclear Medicine and Allied Science (NINMAS) in Dhaka, Bangladesh. The radioactivity concentration   in urine sample is due to intake of I-131, Tc-99m and F-18. The samples have been analyzed using High Purity Germanium (HPGe) detector. The radioactivity of I-131 and Tc-99m was found 0.91 ± 0.26 BqL-1 to 504.49 ± 6.03 BqL-1 and 0.15 ± 0.21 BqL-1 to 191.19 ± 6.98 BqL-1 respectively. Radioactivity of F-18 was found from 0.031 ± 0.022 BqL-1 to 0.282 ± 0.065 BqL-1. The effective doses of occupational workers have been also calculated using the radioactivity concentration and the dose coefficient according to ICRP publication 78.Jagannath University Journal of Science, Volume 11, Number 1, June 2024, pp. 64−80